Epitaxial Metal Halide Perovskites by Inkjet-Printing on Various Substrates - Sytnyk, Mykhailo; Yousefi-Amin, Amir Abbas; Freund, Tim; Prihoda, Annemarie; Götz, Klaus; Unruh, Tobias; Harreiß, Christina; Will, Johannes; Spiecker, Erdmann; Levchuk, Jevgen; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2020)
Metal-halide-perovskites revolutionized the field of thin-film semiconductor technology, due to their favorable optoelectronic properties and facile solution processing. Further improvements of perovskite thin-film devices require structural coherence on the atomic scale. Such perfection is achieved by epitaxial growth, a method that is based on the use of high-end deposition chambers. Here epitaxial growth is enabled via a approximate to 1000 times cheaper device, a single nozzle inkjet printer. By printing, single-crystal micro- and nanostructure arrays and crystalline coherent thin films are obtained on selected substrates. The hetero-epitaxial structures of methylammonium PbBr(3)grown on lattice matching substrates exhibit similar luminescence as bulk single crystals, but the crystals phase transitions are shifted to lower temperatures, indicating a structural stabilization due to interfacial lattice anchoring by the substrates. Thus, the inkjet-printing of metal-halide perovskites provides improved material characteristics in a highly economical way, as a future cheap competitor to the high-end semiconductor growth technologies.
CRIS-Team Scopus Importer:2020-09-11
Keywords: epitaxial growth; inkjet printing; metal-halide-perovskites; single-crystal-microstructures

Fabrication of Bariumtrisulphide Thin Films as Precursors for Chalcogenide Perovskites - Freund, Tim; Cicconi, Maria Rita; Wellmann, Peter (physica status solidi (b), 2022)
Chalcogenide perovskites are a promising and novel class of materials in the fields of solar cells and related subjects. However, the synthesis of thin films of these materials still is troublesome. This work attempts to utilize a phase in the Ba-S phase system with low melting point, namely, BaS3, for the thin-film synthesis of BaZrS3. The successful synthesis of BaS3 thin films is presented and confirmed by field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and Raman analysis. The microstructure of the synthesized BaS3 thin films shows defects and cracks and therefore needs further optimization for the use for BaZrS3 thin-film synthesis. However, the successful synthesis of BaS3 thin films is potentially a great step toward a facile BaZrS3 thin-film synthesis.
CRIS-Team WoS Importer:2022-06-17

Synthesis of BaZrS3 and BaS3 Thin Films: High and Low Temperature Approaches - Freund, Tim; Jamshaid, Sumbal; Monavvar, Milad; Wellmann, Peter (Crystals, 2024)
Current research efforts in the field of the semiconducting chalcogenide perovskites are directed towards the fabrication of thin films and subsequently determine their performance in the photovoltaic application. These efforts are motivated by the outstanding properties of this class of materials in terms of stability, high absorption coefficient near the band edge and no significant health concerns compared to their halide counterparts. The approach followed here is to use stacked precursor layers and is adopted from other chalcogenide photovoltaic materials like the kesterites and chalcopyrites. The successful synthesis of BaZrS3 from stacked layers of BaS and Zr and annealing at high temperatures ( 1100 °C) with the addition of elemental sulfur is demonstrated. However, the film shows the presence of secondary phases and a flawed surface. As an alternative to this, BaS3 could be used as precursor due to its low melting point of 554 °C. Previously, the fabrication of BaS3 films was demonstrated, but in order to utilize them in the fabrication of BaZrS3 thin films, their microstructure and processing are further improved in this work by reducing the synthesis temperature to 300 °C, resulting in a smoother surface. This work lays the groundwork for future research in the fabrication of chalcogenide perovskites utilizing stacked layers and BaS3.
CRIS-Team Scopus Importer:2024-04-05
Keywords: barium trisulphide; chalcogenide perovskites; stacked layers; thin films